PEDAGOGICAL MONITORING OF STUDENT RESEARCH ACTIVITY PERFORMANCE VIA ELECTRONIC PORTFOLIO - T. A. BORONENKO; V. S. FEDOTOVA (Высшее образование в России, 2017)
The purpose of the study is to develop a methodology for assessing the impact of research activities of undergraduate and graduate students via student electronic portfolio. Research methods included analysis of information on existing forms of research activity of bachelor, master and postgraduate students, requirements to the performance of research work on each educational stage. The main result of the study is the positioning of student electronic portfolio as a modern and effective means of monitoring students’ educational achievements, assessing the development of students ‘ professional competencies, solving organization, planning, and implementation problems. This is an effective tool for qualitative/quantitative evaluation of learner’s research activity implemented as part of the educational process and parallel to it. Pedagogical monitoring is characterized as a modern means of monitoring and evaluating the impact of research activities, ensuring the efficiency and availability of information. The authors identify the principles of focus and predictability, objectivity, integrity and continuity, development and self-organization, of regularity and consistency in the implementation of pedagogical monitoring. The paper also grounds relevance of the point rating evaluation of students’ research activity performance as the most adequate and efficient system demonstrating the success of each student. The paper has shown the stimulating effect of the regular pedagogical monitoring of students’ research activities by means of electronic portfolio.